CD4:CD8 lymphocyte ratio as a quantitative measure of immunologic health in HIV-1 infection: findings from an African cohort with prospective data - Tang, Jianming; Li, Xuelin; Price, Matthew A.; Sanders, Eduard J.; Anzala, Omu; Karita, Etienne; Kamali, Anatoli; Lakhi, Shabir; Allen, Susan; Hunter, Eric; Kaslow, Richard A.; Gilmour, Jill (Frontiers in Microbiology, 2015)
In individuals with human immunodeficiency virus type 1 (HIV-1) infection, CD4:CD8 lymphocyte ratio is often recognized as a quantitative outcome that reflects the critical role of both CD4+ and CD8+ T-cells in HIV-1 pathogenesis or disease progression. Our work aimed to first establish the dynamics and clinical relevance of CD4:CD8 ratio in a cohort of native Africans and then to examine its association with viral and host factors, including: (i) length of infection, (ii) demographics, (iii) HIV-1 viral load (VL), (iv) change in CD4+ T-lymphocyte count (CD4 slope), (v) HIV-1 subtype, and (vi) host genetics, especially human leukocyte antigen (HLA) variants. Data from 499 HIV-1 seroconverters with frequent (monthly to quarterly) follow-up revealed that CD4:CD8 ratio was stable in the first three years of infection, with a modest correlation with VL and CD4 slope. A relatively normal CD4:CD8 ratio (>1.0) in early infection was associated with a substantial delay in disease progression to severe immunodeficiency (<350 CD4 cells/l), regardless of other correlates of HIV-1 pathogenesis (adjusted hazards ratio = 0.43, 95% confidence interval = 0.29-0.63, P <0.0001). Low VL (<10,000 copies/ml) and HLA-A*74:01 were the main predictors of CD4:CD8 ratio >1.0, but HLA variants (e.g., HLA-B*57 and HLA-B*81) previously associated with VL and/or CD4 trajectories in eastern and southern Africans had no obvious impact on CD4:CD8 ratio. Collectively, these findings suggest that CD4:CD8 ratio is a robust measure of immunologic health with both clinical and epidemiological implications.